Chronic eosinophilic pneumonia. - Pinheiro, A (1994)
Various types of pulmonary eosinophilia have been known for several years. Chronic eosinophilic pneumonia (original word for Christoforidis and Molnar 1960) is a rare entity whose diagnosis is possible through clinical, laboratory and radiological data. Other non sophisticated data-CAT, bronchoalveolar lavage, transbronchial biopsy, transthoracic biopsy and even thoracotomy can be used. Seriousness can be very high, demanding an urgent diagnosis and treatment.